Implementation Of Video-Based Listening Learning on Simple Story Texts For Grade Iv Elementary School Students in Bandaran 1 - Muhammad Ali Fahmi Ramadan; Qoshrin Tsaniya Aurellia; Nada Nadia; Nurul Aini; Narisa Indi Adesta; Ainur Rofiq Hafsi (Molang: Journal Islamic Education, 2026)
Listening skills form the foundation of language acquisition, yet they remain underemphasized in Indonesian language instruction at the elementary level, partly due to the dominance of lecture-based methods and the limited use of media capable of facilitating simultaneous auditory-visual information processing. This study aims to describe the implementation of animated video-based listening instruction on simple narrative texts and to analyze students' responses to the use of this medium. A descriptive quantitative approach was employed with 12 fourth-grade students at SDN Bandaran 1, Pamekasan, during the even semester of the 2025/2026 academic year. Data were collected through structured observation using four listening competency indicators and a ten-item four-point Likert scale student response questionnaire. Observation results showed that 75.00% of students could identify the story title, 50.00% could recognize the main character, 41.67% could retell the story content, and 25.00% could convey the moral lesson. This achievement pattern indicates that students find it easier to comprehend explicit surface-level information than implicit meaning requiring inferential processing. The student response questionnaire yielded an overall percentage of 82.71% in the very good category, reflecting high student acceptance of animated video media. These findings imply the need for additional scaffolding strategies, particularly to support the development of inferential comprehension in video-based listening instruction.